1998
DOI: 10.1007/bf00703437
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of duplex ultrasound and liquid crystal contact thermography in preclinical detection of deep vein thrombosis after proximal femur fractures

Abstract: During a prospective clinical study the diagnostic value of the two non-invasive examinations colour-coded duplex ultrasound (Duplex) and fluid crystal contact thermography (LCCT) was investigated in relation to phlebography, the standard examination for the diagnosis of deep vein thrombosis (DVT), in 112 patients with proximal femur fractures. In 19% of the patients, DVT was diagnosed by phlebography, with the main localisation in the lower leg in 19 of 21 (90%) thromboses. With a negative prediction value of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…However, widespread adoption of such technology is limited by high capital costs, motion artefacts and inability for use outside of clinical or laboratory settings. Other low-cost thermography techniques have been explored for potential screening of deep venous thrombosis [4][5][6][7] , breast cancer [8][9][10] , spinal root syndromes 11,12 , chronic back pain 13 and even pulmonological diagnostics 14 . Recent work 15,16 demonstrates that electronic temperature-mapping devices can be constructed in ultra-thin, soft and compliant formats, sometimes referred to as 'epidermal' due to the similarity of their physical characteristics to those of the skin itself.…”
mentioning
confidence: 99%
“…However, widespread adoption of such technology is limited by high capital costs, motion artefacts and inability for use outside of clinical or laboratory settings. Other low-cost thermography techniques have been explored for potential screening of deep venous thrombosis [4][5][6][7] , breast cancer [8][9][10] , spinal root syndromes 11,12 , chronic back pain 13 and even pulmonological diagnostics 14 . Recent work 15,16 demonstrates that electronic temperature-mapping devices can be constructed in ultra-thin, soft and compliant formats, sometimes referred to as 'epidermal' due to the similarity of their physical characteristics to those of the skin itself.…”
mentioning
confidence: 99%
“…The latter records and measures body surface temperatures. [12][13][14][15][16][17][18] To date, however, there has been no report on screening for DVT with IRTI. 12 Since then, several studies on LCCT detection and diagnosis of DVT have confirmed that thermography is a highly effective screening method for DVT, with thermography yielded sensitivities of 55%-97%, specificities of 62%-85%, negative prediction values of 94.0%-96.5%, positive prediction value of 67.7%, and 90% agreement between LCCT and phlebography.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the sensitivity and specificity of thermography are lower than those of CPUS, contact thermography with liquid crystal screens has been shown to be a suitable, inexpensive, simple, rapid, and noninvasive screening tool for DVT detection. [12][13][14][15][16][17] Thermography can detect clinically unrecognized thrombosis, identify patients with suspected unilateral lower-limb DVT, and diagnose DVT in high-risk patients. 9,[12][13][14][15][16][17] Noncontact IRTI has been found effective as an adjunctive diagnostic screening test in DVT rabbit models.…”
Section: Variablementioning
confidence: 99%
“…11 Several previous studies have confirmed the effectiveness of contact thermography in detecting various diseases, including DVT. [12][13][14][15][16][17] Infrared thermal imaging (IRTI) is a type of noncontact thermography that uses an uncooled infrared camera to capture the infrared radiation emitted by the body surface, thus measuring and recording body surface temperatures. 11 CPUS requires coupling medium contact, whereas IRTI uses remote capture without contact.…”
Section: Introductionmentioning
confidence: 99%